2021
DOI: 10.1016/j.compbiomed.2021.104295
|View full text |Cite
|
Sign up to set email alerts
|

Targeting multiple conformations of SARS-CoV2 Papain-Like Protease for drug repositioning: An in-silico study

Abstract: Papain-Like Protease (PLpro) is a key protein for SARS-CoV-2 viral replication which is the cause of the emerging COVID-19 pandemic. Targeting PLpro can suppress viral replication and provide treatment options for COVID-19. Due to the dynamic nature of its binding site loop, PLpro multiple conformations were generated through a long-range 1 micro-second molecular dynamics (MD) simulation. Clustering the MD trajectory enabled us to extract representative structures for the conformational space generated. Adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Previous literature has highlighted the potential impact of medicinal plants and their phytoconstituents against SARS-CoV-2 ( Rudrapal et al, 2021 ). Studies have reported that thioflavonoids and epicatechin-3-O-gallate interacted with (binding sites) Mpro and PLpro, and were considered as SARS-CoV-2 inhibitors ( Gogoi et al, 2021 , Ismail et al, 2021 ). Thus, bioactive molecules bind to or interact with the active residues which are present at the binding cavity of Mpro and PLpro.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has highlighted the potential impact of medicinal plants and their phytoconstituents against SARS-CoV-2 ( Rudrapal et al, 2021 ). Studies have reported that thioflavonoids and epicatechin-3-O-gallate interacted with (binding sites) Mpro and PLpro, and were considered as SARS-CoV-2 inhibitors ( Gogoi et al, 2021 , Ismail et al, 2021 ). Thus, bioactive molecules bind to or interact with the active residues which are present at the binding cavity of Mpro and PLpro.…”
Section: Resultsmentioning
confidence: 99%
“…The main protease (Mpro) and the papain-like protease (PLpro) can be targets for anti-SARS-CoV-2 drugs. Research in this direction is prevalent and concerns mainly common natural compounds or repurposing of already used drugs [35][36][37][38]. Studies presented in this article are first concerning the activity of xanthophylls against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…For the PL pro , the docking grid box was centred on the active site (39.64, 30.68, 1.66; size: 20 x 20 x 20 Å) and in the Zn binding site (82.40 x 26.32 x -0.62; size: 20 x 20 x 20Å). The three-dimensional model of Ceftaroline Fosamil, Ceftobiprole, Ceftobiprole Medocaril and their metabolites, were created with Avogadro and MOPAC (PM6 method) (Hanwell et al, 2012;Stewart, 2016Stewart, , 2007, using the dielectric constant of water (78.4), and taking into account the physiological pH equilibrium (7.0-7.4) determined by the Marvin Skecth 17.21.0, ChemAxon program (see Supporting Information (SI) Figures S17- 19("ChemAxon -Software Solutions and Services for Chemistry & Biology," n.d.). This approach used in the optimization of the molecules under analysis aims aproducing the conditions closest to the real environment.…”
Section: Docking Simulationsmentioning
confidence: 99%
“…In PL pro , the Cys111 from the catalytic triad contains the nucleophilic center that directly participates in the cleavage of the peptide bond of pp1a and pp1ab polyprotein from SARS-CoV-2, and the His272 and Asp286 residues participate as an acid-base pair that promotes the thiol deprotonation of Cys111. The resulting thiolate has enhanced nucleophilicity (Anirudhan et al, 2021;Ismail et al, 2021). Thus, blocking the thiol moiety of Cys111 is an important strategy to inhibit PL pro .…”
Section: 24-thiadiazole Containing Drugs and Metabolitesinteraction W...mentioning
confidence: 99%